Disparitas Implementasi Undang-Undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional dalam Pembentukan Kesadaran Hukum Pendidikan sebagai Wujud Bela Negara di Era Globalisasi - Muhammad Abdul Zalil; Alfinto Rizky Susanto; Muhammad Rifqi Rifa’i; Ahmad Muhaimin; Muhammad Thoriq Astari; Muhammad Sahwal; Naufal Rakan Fatih; Andini Namira Oktafiandri (PT Cendekia Education Center, 2026)
This Community Service Program (PKM) activity was carried out at SMK Puspita Bangsa with the title “Disparity in the Implementation of Law Number 20 of 2003 Concerning the National Education System in Forming Legal Awareness of Education as a Form of State Defense in the Era of Globalization.” This activity was motivated by the importance of students’ understanding regarding legal awareness in education and the implementation of state defense values amid the development of globalization. The purpose of this community service activity was to provide students with an understanding of the meaning of state defense, legal awareness of education, and the implementation of Law Number 20 of 2003 concerning the National Education System in everyday life. The implementation method was carried out through legal consultation on May 21, 2026, and evaluation on May 22, 2026, using direct field socialization methods. The activity was conducted interactively through the delivery of materials, discussions, and question-and-answer sessions with participants. The results achieved showed that this activity successfully increased students’ understanding of the meaning of state defense, the importance of legal awareness in education, and the role of the younger generation in maintaining national values in the era of globalization. Thus, this PKM activity made a positive contribution to building legal awareness and the character of state defense within the educational environment.